ANCIENT PERIOD CITY TRADITIONS - Nishanov J. (Bright Mind Publishing, 2025)
The article provides information about the use of the terms “antique”, “antique era” in the process of studying the history of Central Asia in the 4th century BC - 4th century AD, as well as about the traditions of urban planning.
Keywords: “Antique”, “antique era”, archaeologists, Sokhta, Harappa, Mundigak, Altyndepa, Sopollitepa, Zharkotan, Sogd, Kang, Davan, V. Tarn, A. Shoffman.